Diagnostic Test for Analyze Students' Conception in Science Education: A Review Article - Slamet Maulana; Ani Rusilowati; Sunyoto Eko Nugroho; Endang Susilaningsih (International Conference on Science, Education, and Technology, 2023)
Diagnostic tests are a form of evaluation in education that has a high level of urgency because diagnostic tests are able to find the level of studnets’ conceptions. So, this study aims to examine the research that has been carried out related to diagnostic tests for evaluation in education, the possibility of further development, and impact on the implementation of evaluation in education. This research is a review study to analyze research trends regarding diagnostic tests for evaluation in education, the possibilities for their development, and their impact on education. Based on the results of the research and the descriptions, this is certainly an opportunity to conduct research related to diagnostic tests to analyze the level of students’ conceptions in science education. The research related to diagnostic tests for evaluation in the field of education is still very much needed. Opportunities that can be further developed related to related research are the development of diagnostic test materials, forms of diagnostic tests, to the research subjects of the diagnostic tests themselves. This will certainly have an impact on the development of educational evaluation which not only provides alternative evaluation tools for teachers, but also provides clear information about the level of studnets’ conceptions, even to analyze the misconceptions possibility in students, as well as providing information to teachers about the feedback that must be given to the students.